Microplastics Degradation and Characterization - La Nasa, Jacopo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the last decade, issues related to pollution from microplastics in all environmental compartments and the associated health and environmental risks have been the focus of intense social, media, and political attention worldwide. The assessment, quantification, and study of the degradation processes of plastic debris in the ecosystem and its interaction with biota have been and are still the focus of intense multidisciplinary research. Plastic particles in the range from 1 to 5 mm and those in the sub-micrometer range are commonly denoted as microplastics and nanoplastics, respectively. Microplastics (MPs) are being recognized as nearly ubiquitous pollutants in water bodies, but their actual concentration, distribution, and effects on natural waters, sediments, and biota are still largely unknown. Contamination by microplastics of agricultural soil and other environmental areas is also becoming a matter of concern. Sampling, separation, detection, characterization and evaluating the degradation pathways of micro- and nano-plastic pollutants dispersed in the environment is a challenging and critical goal to understand their distribution, fate, and the related hazards for ecosystems. Given the interest in this topic, this Special Issue, entitled "Microplastics Degradation and Characterization", is concerned with the latest developments in the study of microplastics.